PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP MINAT BELI SAMBEL MBEGOR DI JEMBER - Illahi, Dian Septi Riski; Alfan, Afif; Aurellya, Safa Natasha; Hafit, Muhammad Nur; Prabuana, Indra; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2025)
Sambel Mbegor is a restaurant that provides food with one of the typical sambal variants from Jember, East Java. This dish is famous for its spicy, sour and savory taste that is appetizing. This Sambel Mbegor dish uses the basic ingredients of chilies, tomatoes, shallots, garlic, as well as additional natural ingredients such as shrimp paste, which are mashed and mixed until evenly distributed. The uniqueness of mbegor chili sauce lies in the use of special spices and the processing method which is simple but produces a very distinctive taste. This study investigates the role of brand identity, product quality, and price of goods on consumer purchasing interest in the Sambel Mbegor business. The research approach is descriptive quantitative research, where the research population is Sambel Mbegor customers in Jember City. Data collection was carried out through the use of questionnaires and literature reviews, while data was analyzed with the help of the SPSS application. The results of this research show that the brand image, product quality and price of Sambal Mbegor Jember have an influence on consumer buying interest.